SIKAP WANITA USIA REPRODUKTIF TENTANG DETEKSI DINI KANKER PAYUDARA DI PUSKESMAS KEMLAGI MOJOKERTO - Dwi Helynarti Syurandari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
In Indonesia, breast cancer is include second ranks after cervical cancer. BSC (breast self check) is one of the way to detect breast cancer first. In Puskesmas Kemlagi at April 15 2015 majority of 24 respondents (54.2%) did not practice BSC (breast self check), while the purpose of this study is to identify women's attitudes about first detect of breast cancer with BSC practice (check your own breast. This research was an descriptive study, with a population in this study were all women of reproductive age in the age of 15-49 years in Puskesmas Kemlagi Mojokerto which amounted to 926 persons. Samples in this study was part of reproductive age women in the age of 15-49 years in Puskesmas Kemlagi Mojokerto which amounted to 280 persons. The sampling technique with probability sampling techniques with cluster random sampling type. This research was done on June 3 to June 28, 2015. The results from this research were obtained from 280 respondents who have negative attitude about first detect of breast cancer is about 146 respondents (52.1).The conclusion from this research that the reproductive age women’s have negative attitudes about first detect of breast cancer. Because of that it is expected of health workers can provide information about breast cancer and the dangers in order to change women’s attitudes about first detect of breast cancer with BSC practice (check your own breasts).